Hypocalcemia was associated with increased perioperative blood loss and blood transfusion in elderly patients with hip fracture: a retrospective study - Yunqing Zhang; Kun Lu; Qi Liu; Chun Liu; Shilong Su; Chunhua Yang (BMC Surgery)
Abstract Background Serum calcium is the critical coagulation factor in physiological coagulation, and hypocalcemia has been found to be associated with more blood loss in many diseases. The purpose of this study was to explore the effect of hypocalcemia on total blood loss (TBL) and blood transfusion in elderly patients with hip fracture. Patients and methods Elderly patients with hip fracture undergoing surgery in our hospital were included in this study from January 2020 to May 2023. The demographic data, perioperative parameters, hemoglobin, hematocrit, and transfusion requirement were recorded and analyzed. Hypocalcemia was defined as an albumin-corrected calcium level of less than 2.15 mmol/L. TBL of each patient was calculated using the formulas of Nadler and Gross. Blood loss on the 1st and 5th postoperative days was calculated. Results 682 elderly patients with hip fracture were included in the study. On admission, the prevalence of hypocalcemia was 40.47%. Both the TBL on the first day (714.91 ± 396.05 ml vs. 640.31 ± 398.83 ml, P = 0.016) and the fifth day (1035.87 ± 528.77 ml vs. 859.92 ± 434.99 ml, P < 0.001) after operation in the hypocalcemia group were higher than those in the normocalcemia group. The preoperative, postoperative and perioperative blood transfusion rates of hypocalcemia patients were higher than those of the normocalcemia group. Conclusion Hypocalcemia was associated with increased TBL and blood transfusion in elderly patients with hip fracture during the perioperative period.